Estimating the wavelet bispectrum of multiband whistler mode waves - Shah, M. G.; Burgess, D. (Frontiers in Astronomy and Space Sciences, 2024)
Whistler mode waves are one of the dominant plasma emissions occurring in the Earth’s magnetosphere. Using data from the Magnetospheric Multiscale (MMS) mission taken in the outer magnetosphere, we present observations of a multiband whistler event with multiple discrete frequency bands of whistler emission. A newly developed bispectral analysis method, the normalized wavelet bispectrum, is employed to explore the generation mechanism of such whistler mode waves. This method is useful for examining the time-evolving behaviour of coupled oscillatory systems. The wavelet bispectrum analysis of multiband whistlers suggests that the higher-frequency whistler band is possibly generated due to a nonlinear three-wave coupling involving the two lower-frequency whistler bands. The presence of other features such as rising tones provides evidence that multiband whistler events probably involve several different concurrent emission processes.